2013
DOI: 10.3748/wjg.v19.i5.742
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics increase T regulatory cells and reduce severity of experimental colitis in mice

Abstract: Probiotics effectively treat experimental colitis by increasing CD4+CD25+Foxp3+T cell and regulating the balance of Th1 and Th2 cytokines in the colonic mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 27 publications
4
32
1
1
Order By: Relevance
“…Second, probiotics interact with the local immune system. An example is that some probiotic strains can enhance regulatory T cell responses, downregulate the expression of pro-inflammatory cytokines, such as TNF-α and IFN-γ [ 113 , 114 ], and induce the production of a variety of anti-inflammatory cytokines, e.g., IL-10 and TGF-β [ 115 ].…”
Section: Therapeutic Opportunities: Pro/prebiotics Diet Interventionmentioning
confidence: 99%
“…Second, probiotics interact with the local immune system. An example is that some probiotic strains can enhance regulatory T cell responses, downregulate the expression of pro-inflammatory cytokines, such as TNF-α and IFN-γ [ 113 , 114 ], and induce the production of a variety of anti-inflammatory cytokines, e.g., IL-10 and TGF-β [ 115 ].…”
Section: Therapeutic Opportunities: Pro/prebiotics Diet Interventionmentioning
confidence: 99%
“…Bifico capsules were approved as an over‐the‐counter drug by the Chinese regulatory authority, the State Food and Drug Administration, in 2002 . Previous research has shown that Bifico could relieve gastritis induced by Helicobacter pylori and ameliorate experimental colitis caused by DSS in mice . However, the effect of Bifico on CAC has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…23 Previous research has shown that Bifico could relieve gastritis induced by Helicobacter pylori and ameliorate experimental colitis caused by DSS in mice. 24,25 However, the effect of Bifico on CAC has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Macfarlane et al, flora samples in biopsy specimens from the rectums of UC patients were studied through fluorescence in situ hybridization (FISH) with a 16S rRNA probe, and the number of Bifidobacterium in UC patients was about 30-fold less than that in healthy individuals [ 32 ]. Zhao et al found that Bifidobacterium can increase the number of CD4+CD25+Foxp3+ T cells and regulate the balance between Th1 and Th2 cells in the colonic mucosa, thereby reducing intestinal inflammation [ 33 ]. Moreover, Tanabe et al found that Bifidobacterium may suppress the production of the inflammatory factor interleukin- (IL-) 17, thus attenuating intestinal inflammation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%